La gestión del talento humano por competencias en el desarrollo institucional de la cooperativa de ahorro y crédito P.A.I.S. ltda - Espinoza Alvear, Jhoselyn Mishell (2024)
ABSTRACT: This study investigates the impact of human talent management on the institutional development of "Cooperativa de Ahorro y Crédito P.A.I.S. Ltda." The research aims to understand how these competencies affect the cooperative's matrix and promote efficiency, productivity, and individual and collective growth. It draws on quotes from influential authors who have addressed the research topic in their scientific articles, books, and theses to provide a comprehensive understanding of the study. For this study to be possible, surveys were conducted among the employees of the Cooperative, as well as interviews with the General Manager and the head of the agency. During this research, the SPSS statistical software was used to process the data collected through the surveys, as well as to carry out the reliability analysis and verification of the proposed hypotheses. Besides, the Chi Square technique was applied for this purpose. Finally, the conclusion reached is that the management of human talent competencies is closely related to institutional development. The results obtained supported the alternative hypothesis proposed, showing that the management of human talent competencies affects institutional development of “Cooperativa de Ahorro y Crédito P.A.I.S. Ltda.” As a result, it was necessary to design human talent management strategies by competencies for the institutional development of the Cooperative's matrix. With these data obtained, it was necessary to design human talent management strategies by competencies for the institutional development of the Cooperative's matrix. This analysis contributes to and strengthens the cooperative's ability to achieve its long-term objectives.